Analysis of Water Quality Parameters of Mangrove Waters Aek Horsik Village Tapanuli Tengah District for Fishery Cultivation - Batubara, Lenni Wahyuni; Santikawati, Susi; Gulo, Wirni Ansyah (Faculty of Fisheries and Marine, Universitas Riau, 2024)
Water quality is a condition of water based on physical, chemical, and biological properties that suit the needs of aquatic organisms and humans, such as water quality in fisheries, agriculture, drinking water, hospitals, and industry. This research aims to analyze the feasibility of water quality parameters for mangrove waters in AekHorsik village, Tapanuli Tengah Regency, as a location for developing fisheries cultivation. The research method used is a descriptive method with quantitative data analysis. The results of this research show that the chemical parameters obtained were pH (7.3-7.9 ppt), salinity (12-22 ppt), ammonia (0.25-0.29 mg/L), and DO (5.0-55 ppm). The physical parameters obtained are temperature (30-32oC), brightness (0.53-0.95 m), current speed (0.05-0.08 m/sec), and depth (0.53-0.95 m). The biological parameters obtained were phytoplankton abundance of 3,400-6,100 14,450 ind/L and macrozobenthos abundance of 104.9-179.0 ind/m2. Based on these results, it can be seen that the water quality parameters of mangrove waters in AekHorsik village, Tapanuli Tengah Regency, are suitable as a location for developing fisheries cultivation